Industrial Training Report: Perpustakaan Tunku Tun Aminah, Universiti Tun Hussein Onn / Nurmaizatul Nadiah Ahmad Zawawi - Ahmad Zawawi, Nurmaizatul Nadiah (Faculty of Information Management, 2018)
The Industrial Training is a subject IMC690 for every student Part 7, Bachelor of Science in Information Studies (Hons.) Library and Information Management to fulfil this subject with prepared the industrial training report before finishing their degree. The industrial training report contains the activities for every departments in the industry they applied, special projects, knowledge gained, personal thought, lesson learnt, and the limitations and recommendations. This task need to be finished during 5 months internships in the Tunku Tun Aminah Library. In this report, it is contain the background of Tunku Tun Aminah Library, services, facilities, special collections, the organizational structure in the library, and organization information such as the departmental structures and these functions. The reports also have all the details of the activities and program have been done in the Tunku Tun Aminah Library from August until December